2007
DOI: 10.1038/nature05768
|View full text |Cite
|
Sign up to set email alerts
|

Disulphide-isomerase-enabled shedding of tumour-associated NKG2D ligands

Abstract: Tumour-associated ligands of the activating NKG2D (natural killer group 2, member D; also called KLRK1) receptor-which are induced by genotoxic or cellular stress-trigger activation of natural killer cells and co-stimulation of effector T cells, and may thus promote resistance to cancer. However, many progressing tumours in humans counter this anti-tumour activity by shedding the soluble major histocompatibility complex class-I-related ligand MICA, which induces internalization and degradation of NKG2D and sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
311
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 338 publications
(320 citation statements)
references
References 27 publications
5
311
2
2
Order By: Relevance
“…Other surface proteins such as CD44 and PBEF might serve as the relevant targets for the antibody-dependent cytotoxicity of RENCA cells, although this will require additional investigation. Nonetheless, we confirmed the strong surface expression of PDI and ERp5 in multiple murine and human cancer cell lines, 53 including tumor types similar to the patients reported here. Unfortunately, autologous cancer cells were not available for characterization, as these had been used for vaccine manufacture.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Other surface proteins such as CD44 and PBEF might serve as the relevant targets for the antibody-dependent cytotoxicity of RENCA cells, although this will require additional investigation. Nonetheless, we confirmed the strong surface expression of PDI and ERp5 in multiple murine and human cancer cell lines, 53 including tumor types similar to the patients reported here. Unfortunately, autologous cancer cells were not available for characterization, as these had been used for vaccine manufacture.…”
Section: Discussionsupporting
confidence: 67%
“…Among the antigens, the human ortholog of PDI manifested immunogenicity in a limited number of cancer patients, whereas the closely related disulfide isomerase ERp5 elicited humoral reactions that were temporally associated with clinically significant anti-tumor effects in 4 different solid and hematologic malignancies. Because ERp5 facilitates immune escape through the enhancement of MICA shedding 53 and may also promote tumor cell invasion through modifying surface thiols, 56,57 our results raise the possibility that this disulfide isomerase may be a useful target for cancer immunotherapy.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…11 Especially for MICA and ULBP2 molecules it could be shown that considerable amounts are shed from tumor cells by the action of disulfide isomerase, ERp5 and metalloproteases. [39][40][41] Thus, cell turnover and shedding have to be taken into consideration as mechanisms for the release of NKG2DL molecules.…”
Section: Discussionmentioning
confidence: 99%